Impact of Movement Control Order to Busıness Sustaınabılıty Durıng Covıd-19 Pandemıc: a Case of Mıcro Small and Medıum Enterprıses in Indonesıa and Malaysıa - Slamet Widodo; Seprianti Ekaputri; Gerry Suryosukmono (APMBA (Asia Pacific Management and Business Application), 2022)
The COVID-19 pandemic crisis has created an opportunity for SMEs to improve the quality of their products or services and develop various strategies for offering goods or services based on their business concerns. COVID-19 should not be an impediment to SMEs increasing sales because SMEs can promote their sustainability business. The impact of the COVID-19 pandemic on business sustainability among micro-SMEs in Indonesia and Malaysia is highlighted in this paper. In this case, SMEs Indonesia, as a support for national economic activity in Indonesia, have been severely impacted not only in terms of total production and trade value, but also in terms of the number of workers who have lost their jobs as a result of the pandemic. We use survey methods and structured interviews with the business owner. Because of their small size, Micro SMEs are relatively adaptable, allowing them to change their business models quickly. SMEs with a large number of employees, on the other hand, will find it difficult to maintain overhead costs and implement changes in their business direction. SME business models must be reassessed in light of the new normal, post-MCO. They must reassess market expectations and become more aware of shifting habits. SMEs must investigate new markets and customer segments, launch new products, redesign the size and number of packages that are appropriate and relevant for the new market, and ascertain consumer desires. During the COVID-19 outbreak, small and medium-sized businesses ensure that their operations survive, adapt, and continuously improve productivity. We observe some of the business owners to learn what they can do to reduce the impact of the pandemic on their operations, ensure business continuity, and deliver better results in times of crisis. Twenty-five business owners (SMEs) share their experiences in the aftermath of the COVID-19 pandemic. The most difficult challenge for businesses during the pandemic is how to survive persistently and creatively. This requires business owners to optimistically modify their business models, and some business owners radically modify their business models to survive. While geographically diverse and each serving a different consumer, the five businesses profiled below all reflect the realities that the small business community is facing during this trying time.